The role of ethics in the process of technology transfer and development of 206 Peugeot - Mazlomi, Aliakbar; Mohd Yusuff, Rosnah (Engg Journals Publications, 2011)
Looking at the past history we find that the first phenomenon of technology transfer was taught by people who were traveling to another community and bring their technology, they move. After the industrialization, transfer of knowledge from individuals to maintain their importance. However, now the situation for developing countries is controversial because it denied people with technical skills from developed countries to developing countries do not migrate, but the reverse is the professionals that are developing countries to developed countries loan go. Until developing countries can train your human resources specialist, they powerful companies overseas are the means of technology transfer, whether through direct investment, and whether through the sale of licenses and other means. (Noble, p. 105 - 106, 1367) Technology transfer is an important issue that should be given the capacity of countries to assess the possibility of application, absorption and its compatibility with local conditions to increase. Ie the transfer of technology and gain access to technology for its effective use for economic development and growth of countries relatively backward technology provides. (Archibugi, 2003) Today, the role of ethics in technology transfer and development is of great importance. The meaning of ethics and technology than are harvested, ethical values that have roles in the formation of modern technology. Another meaning of ethics and technology than is reached, that moral people who are dealing with technology, they must observe. It also includes technology to those that exist and sets it to those who apply and who are the analysis and criticism. In this article factors and ethical factors in the process of technology transfer and development for Peugeot 206 in Iran Khodro Company has been studied. For this purpose a questionnaire to determine and evaluate factors is designed and results are analyzed.